REDUPLIKASI BAHASA MELAYU JAMBI DI DESA KARMEO KECAMATAN BATIN XXIV KABUPATEN BATANGHARI - Roni Apriadi; Kamaruddin Kamaruddin; Akhyaruddin Akhyaruddin (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Reduplication of Jambi Malay in Karmeo Village, Batin XXIV District, Batanghari Regency. The purpose of this study is to describe the use of reduplication or repeated words in Karmeo Village from three aspects: form, process, and meaning. The data in this study are in the form of informants' utterances, which can be found in Karme Village. The method used in this research is descriptive qualitative. Data collection techniques used recording techniques, involvement-free listening techniques, and note-taking techniques. The data analysis technique uses the Miles and Huberman model technique. The results of this study found that there were four forms of reduplication: (1) whole reduplication, (2) partial reduplication, (3) incremental reduplication, and (4) reduplication with phoneme variations. This study also found five reduplication processes and 10 reduplication meanings in Jambi Malay in Karmeo Village, Batin XXIV District, Batanghari Regency.